2021
DOI: 10.3390/biom11111568
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Based Organoiron Dendrimers as Promising Anti-Inflammatory, Anticancer, and Antimicrobial Drugs

Abstract: Designing nanocarriers with actions directed at a specific organ or tissue is a very promising strategy since it can significantly reduce the toxicity of a bioactive drug. In this study, an organometallic dendrimer was used to synthesize a biocompatible drug delivery system by attaching aspirin to the periphery of the dendrimer. Our goal is to enhance the bioavailability and anticancer activity of aspirin and reduce its toxicity through successive generations of organoiron dendrimers. The biological activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…We chose to use chitosan as a promising natural biopolymer because of its special qualities, including its innate antimicrobial qualities, natural abundance, adaptability, nontoxicity, and biodegradability [34]. We combined its use with aspirin with its assumed antimicrobial properties to maximize the antibacterial efficacy [35]. We examined their effect phenotypically by detecting the AHL production using A. tumefaciens as a biosensor, and analyzing different virulence factors, e.g., motility, pyocyanin production, and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use chitosan as a promising natural biopolymer because of its special qualities, including its innate antimicrobial qualities, natural abundance, adaptability, nontoxicity, and biodegradability [34]. We combined its use with aspirin with its assumed antimicrobial properties to maximize the antibacterial efficacy [35]. We examined their effect phenotypically by detecting the AHL production using A. tumefaciens as a biosensor, and analyzing different virulence factors, e.g., motility, pyocyanin production, and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, great varieties of exquisite nanomaterials such as liposomes, 9 micelles, 10 dendrimers, 11 mesoporous silica nanoparticles, 12 as well as new-style 2D inorganic nanosheets, 13 have been designed to catalyze the new therapeutic/diagnostic platforms for fighting various cancers. These nanomaterials as drug carriers achieve the drug delivery process by a passive or active target mechanism and unite various therapies, such as chemotherapy, photothermal therapy (PTT), photodynamic therapy (PDT), sonodynamic therapy (SDT) and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest reports concerned PAMAM dendrimers conjugated with 5‐aminosalicyclic acid, using different spacers containing an azo‐bond, suitable for the triggered release by enzyme azoreductase (Wiwattanapatapee et al, 2003), naproxen (Najlah et al, 2006), or ibuprofen (Kolhe et al, 2006). Two recent papers reported the synthesis of arylether organoiron dendrimers bearing either ibuprofen (Abd‐El‐Aziz, Abdelghani, et al, 2021) or aspirin (Abd‐El‐Aziz, Benaaisha, et al, 2021) as terminal functions, from the first to the fourth generation. Several examples of dendrimers functionalized with corticoids such as methylprednisolone (Inapagolla et al, 2010), triamcinolone acetonide (Cho et al, 2021; Kambhampati et al, 2015), and dexamethasone (Soiberman et al, 2017), have been also reported.…”
Section: Introductionmentioning
confidence: 99%